2021
DOI: 10.1080/21655979.2021.2009970
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 silencing suppresses inflammation and oxidative stress of acute respiratory distress syndrome by ferroptosis via inhibition of MAPK/ERK pathway in neonatal mice

Abstract: Neonatal acute respiratory distress syndrome (ARDS) has high morbidity and mortality rates worldwide, but there is a lack of pharmacologic treatment and clinical targeted therapies. In this study, we aimed to explore the effects of Lipocalin-2 (LCN2) on ferroptosis-mediated inflammation and oxidative stress in neonatal ARDS and the potential mechanism. In this study, we established an in vivo ARDS mouse model and an in vitro ARDS cell model by LPS (Lipopolysaccharide) stimulation. Lung tissue injury was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Activation of MAPK signaling induced ferroptosis in human pancreatic islet-cell clusters ( Li and Leung 2020 ). In contrast, inhibition of MAPK signaling suppressed inflammation and oxidative stress of acute respiratory distress syndrome caused by ferroptosis ( Wang et al, 2022 ). In other studies, MAPK signaling was found to control ferroptosis in various cancers including nasopharyngeal carcinoma, hepatocellular carcinoma, osteosarcoma, and non-small cell lung cancer through redox balance ( Poursaitidis et al, 2017 ; Lv et al, 2020 ; Chang et al, 2021 ; He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MAPK signaling induced ferroptosis in human pancreatic islet-cell clusters ( Li and Leung 2020 ). In contrast, inhibition of MAPK signaling suppressed inflammation and oxidative stress of acute respiratory distress syndrome caused by ferroptosis ( Wang et al, 2022 ). In other studies, MAPK signaling was found to control ferroptosis in various cancers including nasopharyngeal carcinoma, hepatocellular carcinoma, osteosarcoma, and non-small cell lung cancer through redox balance ( Poursaitidis et al, 2017 ; Lv et al, 2020 ; Chang et al, 2021 ; He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the other two MAPKs signaling (ERK and P38), they can all be activated by the same stimulation factors such as cytokines, neurotransmitters, hormones, cellular stress, and so on, and undergo the same changes. Many articles related to ferroptosis only detect one of them to characterize the change of ERK and P38 (Yang et al, 2021 ; Wang et al, 2022 ). In this study, we focused on the protective effects of L-F001 on ferroptosis and tentatively evaluated the JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In idiopathic pulmonary fibrosis, Sox9 participates in the migration and survival of fibroblasts [ 44 ]. Several studies reveal the underlying mechanism of ARDS by conducting in vivo mouse model and an in vitro cell model [ 45 , 46 ]. Compared to these publications, we examined not only the effects of miR-338-3p in A549 cells caused by LPS, but also the diagnostic role of miR-338-3p for PARDS patients.…”
Section: Discussionmentioning
confidence: 99%